Day 3 Thu, March 24, 2016 2016
DOI: 10.4043/26470-ms
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Mechanical Weakening of Limestone Due to Supercritical CO2 Injection

Abstract: CO 2 injection into limestone reservoirs is a typical process in enhanced oil recovery operations, and it is also suggested for carbon geo-storage. However, CO 2 , together with water, is acidic and creates medium strength acid (pH value 3-4) at HP/HT (High Pressure/High Temperature) conditions. At the same time, it is well known that carbonates react and dissolve when exposed to acid. It can, therefore, be expected that the limestone properties change significantly during CO 2 injection.We thus hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Two Savonnieres limestone cores were obtained from a quarry in the North-East of France (Lorraine region). Savonnieres limestone is a widely used standard carbonate rock used in many published studies of petrophysical and flow properties [27][28][29][30][31] . The XRD results of the rock show that the cores are almost entirely composed of calcite (>99%).…”
Section: Methodsmentioning
confidence: 99%
“…Two Savonnieres limestone cores were obtained from a quarry in the North-East of France (Lorraine region). Savonnieres limestone is a widely used standard carbonate rock used in many published studies of petrophysical and flow properties [27][28][29][30][31] . The XRD results of the rock show that the cores are almost entirely composed of calcite (>99%).…”
Section: Methodsmentioning
confidence: 99%
“…Civan reported that particle bridging can only occur if the ratio (β) of the pore throat to particle diameter is less than 7. As a result, the permeability can decreases if β < 7 ,,,,,, or increase if β > 7, ,,,, owing to changes in the pore throat size as a result of fine migration. Changes in permeability are thus often expected when clay minerals are present in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been many numerical and experimental studies addressing the time‐dependent geomechanical integrity of sandstone aquifers. Likewise, there are also some experimental research works studying the mineral–CO 2 –brine chemical reactions in carbonate . However, minor attention has been given to the impact of changes in the strength of calcite‐rich limestone and quartz‐rich sandstone upon CO 2 injection.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there are also some experimental research works studying the mineral-CO 2 -brine chemical reactions in carbonate. [27][28][29][30][31] However, minor attention has been given to the impact of changes in the strength of calcite-rich limestone and quartz-rich sandstone upon CO 2 injection. The aim of this study is to propose a numerical model where the thermo-hydro-chemo-mechanical processes could be coupled to evaluate the feasibility of sandstone and carbonate aquifers as potential CO 2 sequestration sites.…”
Section: Introductionmentioning
confidence: 99%